Dragonflight eaudiobook - McCaffrey, Anne (Dragonriders of Pern, 2016)
To the nobles who live in Benden Weyr, Lessa is nothing but a ragged kitchen girl. For most of her life she has survived by serving those who betrayed her father and took over his lands. Now the time has come for Lessa to shed her disguise and take back her stolen birthright. But everything changes when she meets a queen dragon. The bond they share will be deep and last forever. It will protect them when, for the first time in centuries, Lessa's world is threatened by Thread, an evil substance that falls like rain and destroys everything it touches. Dragons and their Riders once protected the planet from Thread, but there are very few of them left these days. Now brave Lessa must risk her life, and the life of her beloved dragon, to save her beautiful world...